La prevención del SIDA en educación secundaria. Aplicación piloto de un programa pedagógico de formación y cambio de actitud - Moliner García, Odet; García López, Rafaela (Revista Española de Pedagogía, 2018)
This article describes the elaboration process, application and evaluation of an AIDS Prevention Programme applied to ESO students through Health Education. Apart from the transmission of information influences the formation and changing of attittudes and the development of the ability successfully confront situations where the risk of HIV infection exist. Techniques for formation of and changc of attittudes, clarification of values and decission taking were used. The obtained results show an increment in the attittudes of tolerance and solidarity with sick and seroposilive people, of responsibility toward the solution of the problem and toward thc rules of preventive sexual behavior, besides an increase of knowledge of the illness.
THE PREVENTION OF AIDS IN SECONDARY EDUCATION. PILOT APPLICATION OF A PEDAGOGICAL PROGRAMME ON EDUCATION AND CHANGE OF ATTITUDES
Keywords: prevention; AIDS/HIV; attitudes; adolescents; programme; Revista Española de Pedagogía